FACTORS INFLUENCING GOVERNMENT EMPLOYEES INNOVATIVE BEHAVIOR : A QUALITATIVE STUDY IN PEKANBARU CITY - Evi Zubaidah,; Tito Handoko,; Muazzinah, (Proceeding International Conference on Social Sciences, 2026)
This study aims to explore innovative behavior among government employees in Pekanbaru City using the Theory of Planned Behavior (TPB) as an analytical framework. A qualitative approach was employed to gain an in-depth understanding of how attitudes toward innovation, subjective norms, and perceived behavioral control are interpreted and experienced by employees within a bureaucratic context. Data were collected through in-depth interviews and document analysis involving civil servants and structural officials in the Pekanbaru City Government. The findings indicate that innovative behavior emerges from a dynamic interaction between personal attitudes, social influences, and perceptions of structural opportunities and constraints. Positive attitudes toward innovation are generally grounded in beliefs about work efficiency, yet they are often accompanied by concerns regarding the risk of failure and bureaucratic consequences. Subjective norms, reflected in support from supervisors and colleagues, along with perceived behavioral control related to the availability of resources and autonomy, are understood as key elements in fostering innovative intentions. Furthermore, organizational context, particularly transformational leadership, psychological safety, and bureaucratic flexibility, plays an important role in translating innovative intentions into actual practices. These findings underscore that fostering innovation in the public sector requires a holistic approach integrating individual, social, and organizational dimensions.